PENGARUH MEDIA PENDINGIN PADA PROSES HARDENING TERHADAP KETANGGUHAN BAJA S45C - Govar Arianzas; Dody Prayitno (Journal of Mechanical Engineering and Mechatronics, 2019)
The purpose of this study was to determine the effect of vegetable oil or water cooling media on the Hardening process on the value of the impact strength of S45C. The research method of the S45C steel sample was heated at 900˚C for 1 hour. The sample then in quenching the medium of water or vegetable oil is then tested for impact using the Charpy method. Research result. The value of impact strength of S45C steel is 0.416 Joule / mm2, Hardening (900˚C, 1 Hour) with Quenching Air media causing the value of impact strength to decrease from 0.416 Joule / mm2 to 0.135 Joule / mm2, Hardening (900˚C, 1 Hour) with media of Vegetable Oil Quenching causes the strength value to increase from 0.416 Joule / mm2 to 2,276 Joule / mm2, Microstructure in S45C steel "Raw Material" is ferrite and pearlite, Microstructure sample code "Quenching Air" is Martensite and Troostite, Microstructure sample code "Quenching MinyakSayur "is Bainit.Keywords. Impact Strength, Hardening, Water, Vegetable Oil.